Design of decoupled controller for TITO system using characteristic ratio assignment - Numsomran, Arjin; Wongkhum, Theerachai; Suksri, Tianchai; Nilas, Phongchai; Chaoraingern, Jutarut (My University, 2007)
Most control performances in actual design are usually defined by the time domain response such as overshoot, rising time, settling time, steady state error, etc.. There are few control design methods, which are able to apply directly to the purpose. The pole placement method is the most popular. The Characteristic Ratio Assignment (CRA) is one technique of pole placement based on defined parameter of characteristic equation. This technique cans adjustment of speed response and the damping ratios by only one parameter. In this paper, CRA is use to design controller for two-input two-output (TITO) systems. By using the decentralized CRA controllers and eliminate interaction between loop transfer function with conventional decoupler design method. Several examples are present to illustrate the effectiveness of the proposed method and compared it with existing ones. It is show that CRA design is stable, robust, whilst giving the desired time domain performance. © ICROS.
Keywords: Characteristic Ratio Assignment (CRA) SISO controllers; Decoupling; TITO systems